Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together Terhadap Peningkatan Keterampilan Sosial Siswa - Rina Maryani; Euis Eka Pramiarsih; Rita Zahara (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
The research conducted is entitled The Effect of Cooperative Learning Model Type Numbered Head Together Against the Improvement of Student Social Skills. This study aims to see the effect of learning models in business communication subjects with efforts to improve students' social skills. The data obtained were in the form of the results of the pretest and posttest observation sheets conducted at each meeting. Statistically, using the normality test, homogeneity test, and t test. To see an increase in students' social skills with a gain test. The results show that there is an increase in students' social skills, this can be seen from the significant average presentation value. The change in improvement can be seen from the results of the observation sheet which contains indicators of social skills which include sharing, working together, helping each other, and mutual respect. Learning with numbered head together type can improve students' social skills. It is recommended for each educator to be able to use the cooperative learning model numbered head together as an alternative learning model in business communication subjects in an effort to improve students' social skills.